“Whatever I said didn’t register with her”: medical fatphobia and interactional and relational disconnect in healthcare encounters - Kost, Carolin; Jamie, Kimberly; Mohr, Elizabeth (Frontiers in Sociology, 2024)
This article focuses on medical fatphobia as a specific phenomenon structuring interactions between patients and healthcare practitioners. Throughout, we use the term 'fat' and 'fatphobia as the preferred terms in the body positivity and fat acceptance communities. It is well-documented that 'fat' people frequently experience negative and highly stigmatizing healthcare encounters where weight is disproportionately centred and over-attributed as a cause of ill-health. This can compound and worsen disordered eating, trigger mental health problems, and lead to healthcare avoidance. Although the regularity and risks of these weight-focused encounters are well-established, there does not yet exist a coherent theoretical framework for understanding such discriminatory practices.In this article, we draw on the experiences of fifteen fat women who are members of a Health At Every Size (HAES) online community to explore how they perceive their fatness impacting medical encounters. Through this data, and specifically drawing on Shim's (2010) framework of 'cultural health capital', we suggest that given the deep purchase of cultural tropes surrounding it, fatness is perceived to embody and therefore confers onto patients, assumptions of low cultural health capital.We argue that ubiquitously characteristic of medical fatphobia is what we call an 'interactional and relational disconnect' between fat patients and healthcare practitioners. We suggest that this disconnect structures fatphobic interactions by over-attributing fatness as the underlying cause of medical problems which entrenches patient and practitioner ambivalence because of a lack of joint decision-making. We argue that interactional and relational disconnect is produced by, sustained by, and reproduces asymmetric power relations between patients and practitioners. While we demonstrate that patients develop tactics to mitigate and manage fatphobia in healthcare encounters, the persistent interactional asymmetry between doctors and patients means these attempts often fail.We conclude with a plea for sociology to take seriously medical fatphobia as a form of intersectional systemic discrimination. While movements like HAES, fat positivity and body acceptance create Formatted: Highlight kinship and support fat patients with self-advocacy in healthcare interactions, we suggest that systemic rather than individual change is necessary for effective healthcare inclusion and interaction.